Riverine habitat specificity constrains dispersion in a Neotropical fish (Characidae) along Southern Brazilian drainages. (16th February 2015) - Hirschmann, Alice; Malabarba, Luiz R.; Thomaz, Andréa Tonolli; Fagundes, Nelson J Rosa
<x xml:space="preserve">Abstract</x> Freshwater fishes often display a marked phylogeographic structure strongly associated with historical and ecological changes in the aquatic environment. Different ecological conditions in the same river drainage may act as permeable barriers to dispersion and gene flow. Previous studies recognized two discrete spatial components for the ichthyofauna in the freshwater coastal drainages of southern Brazil: the lowland fish fauna in the lagoons and the fish fauna of the rivers flowing in the valleys. In order to test if the coastal lagoons may limit the dispersion of a riverine species, we describe the phylogeographic structure among populations of Cyanocharax itaimbe, a species endemic to this region. We analysed 55 specimens characterized for two mitochondrial and one nuclear genes. Sequences were analysed using gene trees and species tree approaches, together with standard population genetics methods. Molecular analyses indicated three evolutionary groups which diverged from each other between an estimated 1, 600, 000 and 450, 000 years before the present. However, two currently isolated river systems share the same evolutionary clade, whereas a single drainage contains two different lineages. Our results indicate strong genetic structure among populations along with generally conserved morphology. The strong genetic structure among populations living in the same drainage system may be explained by ecological differences between lagoons and rivers (or palaeochannels) that act as barriers to dispersion.